Influence of Digital Technologies and Framework Design on the Load to Fracture of Co‐Cr Posterior Fixed Partial Denture Frameworks. Issue 7 (23rd December 2021) - Tobar, Celia; Rodriguez, Veronica; Lopez‐Suarez, Carlos; Pelaez, Jesus; Suarez, Maria J.
Abstract: Purpose: To compare the load to fracture of cobalt‐chromium (Co‐Cr) 3‐unit posterior fixed partial denture (FPD) frameworks manufactured by conventional and digital techniques and to evaluate the influence of the framework design on the fracture load. Material and methods: Eighty 3‐unit Co‐Cr posterior FPD frameworks were fabricated with two designs: intermediate pontic (n = 40) and cantilever (n = 40). Each design was randomly divided into four groups (n = 10): casting, direct metal laser sintering, soft metal milling, and hard metal milling. After thermal cycling, all specimens were subjected to a 3‐point bending test until fracture. Data were statistically analyzed using one‐way ANOVA, Welch and Brown‐Forsythe test, Ryan‐Einot‐Gabriel‐Welsch F and Tamhane T2 post hoc test, Student's t test, and Weibull statistics (α = 0.05). Results: Significant differences ( p < 0.001; F = 39.59) were found among intermediate pontic frameworks (except between laser sintering and hard metal milling), and cantilevered frameworks (F = 36.75) (except between laser sintering and hard metal milling, and casting and soft metal milling). The cantilever groups showed load to fracture values significantly lower than those of the intermediate pontic ( p < 0.001; F = 28.29). The Weibull statistics corroborated the results. Conclusions: Hard metal milling and laser sintered frameworks exhibited the highest load to fracture values. However, all tested frameworks demonstrated clinically acceptable load to fracture values. The framework design directly affected the fracture load, with drastically lower values in cantilevered frameworks.